Volume 3: Biomedical and Biotechnology Engineering 2017
DOI: 10.1115/imece2017-72219
|View full text |Cite
|
Sign up to set email alerts
|

Computer Assisted Design and Structural Topology Optimization of Customized Craniofacial Implants

Abstract: Modern design and manufacturing engineering technologies have greatly improved the way in which modern craniofacial implants are designed and fabricated. However, few efforts have been made in order to optimize their design. While the weight of polymer-based implants (e.g. PMMA implants) may not affect the patient’s comfort, the higher weight of metal-based implants (e.g. titanium implants), could greatly affect the patient’s comfort, causing in some cases nuisances and imbalance problems. Thus, the optimizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Moreover, poorly shaped prostheses and implants are difficult to locate and secure in place, increasing the surgical time and risk of infection, and in some cases, they are also ineffective [ 3 ]. Thus, in order to enhance the quality and effectiveness of prostheses and implants, several research works have focused on the development of new approaches for the design and fabrication of prostheses and implants based on the use and integration of engineering technologies, for example [ 2 15 ]. The results have shown that modern engineering technologies allow the design and fabrication of customized prostheses and implants, with benefits in terms of effectiveness, accuracy, fabrication and implantation time, cost, and safety.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, poorly shaped prostheses and implants are difficult to locate and secure in place, increasing the surgical time and risk of infection, and in some cases, they are also ineffective [ 3 ]. Thus, in order to enhance the quality and effectiveness of prostheses and implants, several research works have focused on the development of new approaches for the design and fabrication of prostheses and implants based on the use and integration of engineering technologies, for example [ 2 15 ]. The results have shown that modern engineering technologies allow the design and fabrication of customized prostheses and implants, with benefits in terms of effectiveness, accuracy, fabrication and implantation time, cost, and safety.…”
Section: Introductionmentioning
confidence: 99%